Offering an Interpretation of Prior Talk in Everyday Interaction: A Semantic Map Approach. Issue 4 (21st April 2022) - Zinken, Jörg; Küttner, Uwe-A.
ABSTRACT: Sometimes in interaction, a speaker articulates an overt interpretation of prior talk. Such moments have been studied as involving the repair of a problem with the other's talk or as formulating an understanding of the matter at hand. Stepping back from the established notions of formulations and repair, we examine the variety of actions speakers do with the practice of offering an interpretation, and the order within this domain. Results show half a dozen usage types of interpretations in mundane interaction. These form a largely continuous territory of action, with recognizably distinct usage types as well as cases falling between these (proto)typical uses. We locate order in the domain of interpretations using the method of semantic maps and show that, contrary to earlier assumptions in the literature, interpretations that formulate an understanding of the matter at hand are actually quite pervasive in ordinary talk. These findings contribute to research on action formation and advance our understanding of understanding in interaction. Data are video- and audio-recordings of mundane social interaction in the German language from a variety of settings.